Data: Indicators of Suspended Sediment Transport Dynamics in Rivers - hun Shin, Jae; Grabowski, Robert C.; Holman, Ian P. (Cranfield University, 2023)
The dataset contains SS dynamics indicator calculation results for contiental USA, Honolulu and Puerto Rico. The indicators represent magnitude, frequency and timing. This secondary data has been created without gap filling.
Keywords: suspended sediment concentration'